Sequenciamento, síntese, atividade biológica, estudos biofísicos e estudos estruturais por RMN de três peptídeos isolados da secreção cutânea do anuro Leptodactylus labyrinthicus - Karla Aparecida Guimarães Gusmão (2016)
The mechanisms of action and the biological potential of antimicrobial peptides suggest that these compounds can be used as alternatives for new therapies. The availability of these compounds from several different natural sources has opened an avenue for the discovery of new biologically active molecules. Up to our knowledge, only two peptides isolated from the frog Leptodactylus labyrinthicus, namely pentadactylin and ocellatin-F1, have shown antimicrobial activities, therefore, in order to explore the antimicrobial potential of this species, we have characterized three novel peptides isolated from the anuran skin secretion, as well as investigated their antimicrobial activities, membrane interactions and high-resolution three-dimensional structures. Three peptide sequences were determined by automated Edman degradation and higher amounts of these compounds were prepared by solid-phase synthesis. The antimicrobial activity was tested using Gram-positive and Gram-negative bacteria and two fungal strains. The haemolytic properties of the peptides was also investigated in assays with rabbit blood erythrocytes. The conformational preferences of the peptides and their membrane interactions have been investigated by nuclear magnetic resonance (NMR) and circular dichroism (CD) spectroscopy and liposome dye release assays. The amino acid compositions of three ocellatins were determined and the sequences exhibit 100 % homology for the first 22 residues (Ocellatin-LB1 sequence). Ocellatin-LB2 carries an extra Asn residue and Ocellatin-F1 extra Asn-Lys-Leu residues at C-terminus. Ocellatin-F1 presents a stronger antibiotic potential and a broader spectrum of activities compared to the other peptides. The membrane interactions and pore formation capacities of the peptides correlate directly with their antimicrobial activities, i.e., Ocellatin-F1 > Ocellatin-LB1 > Ocellatin-LB2. Both CD and NMR spectroscopies reveal that all peptides acquire high helical contents in membrane environments and stronger peptide-membrane interactions. Despite the high sequence homology, the structural stabilities near the C-terminus are different for the three peptides. Ocellatin-F1 shows in average stronger helical propensities and a higher structural degree near the C-terminus, especially when compared to Ocellatin-LB2. The obtained results indicate that the three extra amino acid residues at the Ocellatin-F1 C-terminus play an important role in promoting stronger peptide-membrane interactions, antimicrobial properties and the structural stability of the peptide C-terminus. The extra Asn-23 residue present in Ocellatin-LB2 sequence seems to decrease its antimicrobial potential and the strength of the peptide-membrane interactions.